Community Ecosystem Mapping: A Foundational Step for Effective Community Engagement in Research and Knowledge Mobilization - Tanvir C. Turin; Mashrur Kazi; Nahid Rumana; Mohammad A. A. Lasker; Nashit Chowdhury (SAGE Publishing, 2023)
Community engagement is a key strategy for achieving various goals, such as social and environmental change, sustainable development, health promotion, and community building. It involves collaborations and partnerships with the community that help mobilize resources, impact systems, rectify partner dynamics, and function as catalysts for modifying policies, programs, and practices. It also ensures mutual trust among all parties involved, giving community members greater personal agency and involvement potential. We have learned a range of practical aspects of community engagement with communities, particularly with immigrant/racialized communities, by running a community-engaged program of research on the health and wellness issues of immigrant/racialized communities in Calgary, Canada. In this article, we focus on a crucial early step of community engagement-understanding the community ecosystem. The community ecosystem refers to its human, social, and cultural makeups. Understanding this ecosystem requires conscious efforts to comprehend the demography, participate in socio-cultural events, identify community spots, reach out to hard-to-access groups, find the community champions and communication channels/organizations, and reaching out to them to establish relationships. Understanding the community ecosystem allows us to identify the pivotal factors, key actors, and pulse of the community that we are engaging with. This enables us to build mutual trust and goals for research and knowledge mobilization. Subsequently, an empowered, continual, and collaborative partnership becomes possible, resulting in sustained and desirable outcomes.